2020
DOI: 10.3390/su12062419
|View full text |Cite
|
Sign up to set email alerts
|

Precision Irrigation Strategies for Sustainable Water Budgeting of Potato Crop in Prince Edward Island

Abstract: Climate change induced uneven patterns of rainfall emphasize the use of supplemental irrigation in rainfed agriculture. The Penman-Monteith method was used to calculate supplemental irrigation for water budgeting of a potato crop in Prince Edward Island, Canada. Cumulative gaps between rainfall and crop evapotranspiration (ETc) during August and September of the study years were due to high crop coefficient factor, justifying the need for supplemental irrigation. Pressurized irrigation systems, including sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 25 publications
4
42
0
Order By: Relevance
“…fields in New Brunswick and Prince Edward Island [33], while the slope and elevation of agricultural fields explained 22-36% of variation in the tuber yield of these regions [34]. Afzaal et al [35] reported that supplemental irrigation and irrigation application techniques varyingly affected the tuber yield especially in rainfed areas due to uneven rainfall patterns. Potato tuber yield also depends on the tuber seed quality, soil management practices, nitrate contents in the soil, fertilizer, water management practices, and chemical and bio-fertilization [36][37][38][39].…”
Section: Comparative Analysis Of Machine Learning Algorithmsmentioning
confidence: 99%
“…fields in New Brunswick and Prince Edward Island [33], while the slope and elevation of agricultural fields explained 22-36% of variation in the tuber yield of these regions [34]. Afzaal et al [35] reported that supplemental irrigation and irrigation application techniques varyingly affected the tuber yield especially in rainfed areas due to uneven rainfall patterns. Potato tuber yield also depends on the tuber seed quality, soil management practices, nitrate contents in the soil, fertilizer, water management practices, and chemical and bio-fertilization [36][37][38][39].…”
Section: Comparative Analysis Of Machine Learning Algorithmsmentioning
confidence: 99%
“…It has been reported that rainfed potato crop management may shift to irrigation, a necessary condition to reach a yield above the potential in the Quebec region (Parent and Anctil, 2012). In addition, climate changes may increase the use of irrigation to avoid periods of drought due to irregularity and poor distribution of precipitation (Afzaal et al, 2020). Thus, irrigation practices will inevitably be more common, which subsequently increase the pressure on local water resources since only 10% can be reused (Shaffer and Runkle, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although the farmers cannot control rain, proper irrigation scheduling can prevent the leaching of unused plant nutrients in case of continuous drought periods. Changing patterns of rain caused by climate change would bring possible drought, necessitating irrigation of crops for parts of the world that are rain-fed and do not currently need supplemental irrigation [59].…”
Section: Effect Of Rate Of Amendment Applicationsmentioning
confidence: 99%